Magnetic Resonance Contrast Agents: From the Bench to the Patient - Lorusso, Vito; Pascolo, Lorella; Fernetti, Cristina; Anelli, Pier L.; Uggeri, Fulvio; Tiribelli, Claudio (Current Pharmaceutical Design, 2005)
Magnetic Resonance Imaging is gaining a prominent role in the routine clinical investigation. To further improve this technique it is crucial that contrast agents are developed with more optimal organ specificity. This will not only result in a better diagnostic efficiency but also in a reduction of the amount of the agent administered. A combination of techniques has been employed to increase the target selectivity of the contrast agent and thereby the feasibility to visualize different organs. The organ targeting is based on the understanding of the mechanisms involved in the interaction of the agent with plasma proteins (albumin in particular) as well as the different membrane transporters involved in the uptake and in the excretion of the agent from the organ. The physicochemical properties of the contrast agents play a major role in the interaction with these various proteins. In this review we address the relationship between the structure of the contrast agents and their binding to different plasma proteins and membrane transporters in different organs, with special reference to the liver and kidney. The present and potentially future applications of these concepts in the clinical setting are also discussed.
Keywords: plasma protein binding